PARASITIC PROFILE OF FIVE SPECIES OF TERRESTRIAL Achatina SNAIL IN CROSS RIVER STATE, NIGERIA: PUBLIC HEALTH IMPLICATIONS - MBAH, JENAVINE ONYINYE; OSONDU-ANYANWU, CHINYERE; IMALELE, EDEMA ENOGIOMWAN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
A total of 760 snails of the genera Achatina, belonging to five species (Achatina achatina, Achatina belteata, Achatina degneri, Achatina fulica and Achatina marginata) were sampled between January and August 2021, from six communities located in six Local Government Areas (LGAs) in the Central Senatorial District, Cross River State. A. achatina was the most abundant species collected (32.89%) while A. degneri was the least collected (11.19%). A greater number of Achatina snails were collected in the wet season than in the dry season with no observed dominance of any of the species. Overall, 319 (42%) snails were infected with parasites. A. fulica had the highest prevalence of parasitic infection (50.50%) while A. marginata had the least parasitic infection (28%). Snail species sampled in Boki LGA had the highest prevalence of parasitic infection (56.25%), while Obubra LGA recorded the least prevalence (21.28%). Mean intensity of Angiostrongylus spp. in A. achatina was 4.780 (4.56 – 5.00; 95% CI), while Strongyloides spp. was 4.667 (4.11-5.22; 95%CI). Testing parasite species diversity in the snail species assessed using diversity indices, A. balteata recorded the highest values for Shannon-Wiener (1.653) and Margalef’s indices (1.995), and also for species dominance using the Simpson index (0.22). Public health education and provision of adequate toilet facilities are recommended for control of snail-borne parasites.